Socio Economic, Lifestyle and Health Factors Influencing the Nutritional Status of Subjects with Colorectal Cancer in Calicut District of Kerala, India - Aparna S Gopakumar; Kavita M S and Karuna M S (IOSR Journal of Dental and Medical Sciences, 2015)
Colon and rectal cancer is one of the common cancers among men and women from the Indian subcontinent. Faulty dietary habits and defective life style patterns resembling lack of exercise and smoking, physical status such as overweight have been proven to have serious impact in the etiology of colorectal cancer. The study comprises the documentation of the socio economic and lifestyle pattern of 100 newly diagnosed subjects with colorectal cancer. All the subjects were selected at random from Calicut District of Kerala, India. The selected patients were interviewed for collecting data using a well-structured schedule. Based on the findings of the study, it was concluded that inappropriate life style is a major etiological factor in colorectal cancer development. Underprivileged socio economic status, defective personal habits, inadequate exercise and sleeping patterns were the major physiognomies observed among the subjects, which might have contributed to the development of colorectal cancer.